Characteristics of solar wind rotation. Issue 3 (2nd September 2019) - Li, K J; Feng, W
ABSTRACT: Over 54 yr of hourly mean value of solar wind velocity from 1963 November 27 to 2017 December 31 are used to investigate characteristics of the rotation period of solar wind through autocorrelation analysis. Solar wind of high velocity is found to rotate faster than low-velocity wind, while its rotation rate increases with increasing velocity, but in contrast for solar wind of low velocity, its rotation rate decreases with increasing velocity. Our analysis shows that solar wind of a higher velocity statistically possesses a faster rotation rate for the entire solar wind. The yearly rotation rate of solar wind velocity does not follow the Schwable cycle, but it is significantly negatively correlated to yearly sunspot number when it leads by 3 yr. Physical explanations are proposed to these findings.